2017
DOI: 10.1108/lm-07-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Mission statements in academic libraries: a discourse analysis

Abstract: Purpose The purpose of this paper is to determine how academic library mission statements are related to their parent institution mission statements. Design/methodology/approach Using a random sample of the US colleges and universities, library and their respective college or university mission statements were compared using discourse analysis. Findings This study shows a very weak link between college or university mission statements and library mission statements in the majority of cases. Originality/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Therefore, the awareness of the users' information needs could play a crucial role in planning for libraries' future. Wadas (2017) also, by discussing the importance of libraries' activities for parent institutions, reported a very weak relationship between libraries and universities' mission statement (Wadas, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the awareness of the users' information needs could play a crucial role in planning for libraries' future. Wadas (2017) also, by discussing the importance of libraries' activities for parent institutions, reported a very weak relationship between libraries and universities' mission statement (Wadas, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this qualitative research, the data were collected by semi-structured interview form. Some previous related studies have identified several factors for the success and failure of library strategic plans (Matthews and Walton, 2014;Mohammad Esmaeil, 2014;Smith, 2004;Wadas, 2017). To develop this interview guide, factors influencing different parts of the strategic plan including goals, missions, values, strengths and weaknesses were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Learning and teaching have been part of the core mission of academic libraries for decades (Aldrich, 2007;Bangert, 1997;Wadas, 2017), but the way libraries fulfil their educational responsibilities is continually evolving in response to changes in pedagogy, technology, the economy, society, and the policies and strategies of their parent institutions. The "demand for increased flexibility of pace, place and delivery" (HEA, 2015) as a result of financial retrenchment, marketisation and differentiation in higher education (in the UK and elsewhere) and of developments in pedagogies has meant, in theory at least, that a holistic approach to learning and the student experience is now usual practice, as is acceptance that this will involve partnership and collaboration from across an institution.…”
Section: Learning and Teaching In Academic Librariesmentioning
confidence: 99%
“…Others channel attention to hybrid libraries' mission (Von Elm and Trump, 2001). Wadas (2017) discusses the relationship between university libraries' mission and the university served. In an earlier paper, Wilson (1988) connects academic libraries' mission to information science.…”
Section: Literature Review: Mission Statement and National Librariesmentioning
confidence: 99%